2021
DOI: 10.15587/1729-4061.2021.239102
|View full text |Cite
|
Sign up to set email alerts
|

Determination of influence of pH on reaction mixture of ferritation process with electromagnetic pulse activation on the processing of galvanic sludge

Abstract: This paper considers prospects for increasing the level of environmental safety of industrial enterprises as a result of the implementation of resource-saving technology of processing galvanic sludge using the ferritization method. The effectiveness of the use of electromagnetic pulse discharges for resource-saving activation of the ferritization process with the extraction of heavy metal ions from sludge (Fe, Ni, Cu, Zn) has been confirmed. The influence of key parameters of the process such as the pH value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…The data of structural analysis of sediment samples correlate well with the results of electron microscopy of ferrite sediment samples [21]. They showed the presence of crystals of irregular spherical shape in the pore space.…”
Section: Fig 2 Dependence Of the Residual Concentrations Of Heavy Metal Ions On The Volumetric Aeration Rate During The Electromagnetic Psupporting
confidence: 78%
See 1 more Smart Citation
“…The data of structural analysis of sediment samples correlate well with the results of electron microscopy of ferrite sediment samples [21]. They showed the presence of crystals of irregular spherical shape in the pore space.…”
Section: Fig 2 Dependence Of the Residual Concentrations Of Heavy Metal Ions On The Volumetric Aeration Rate During The Electromagnetic Psupporting
confidence: 78%
“…A significant drawback of existing technologies based on hydrophase ferritization is the implementation of the process at temperatures above 75 °С, which requires significant energy costs. In [20], it was shown that an alternative to thermal hydrophase ferritization is the activation of the process by electromagnetic pulse discharges at a process temperature of about 20 ° C. The course of the process of hydrophase ferritization is significantly influenced by the ratio of the concentration of ferrum ions and other heavy metals extracted from the solution [21]. At the same time, the cleaning efficiency largely depends on the pH value of the solution, the temperature and duration of the phase formation process [18].…”
Section: Introductionmentioning
confidence: 99%
“…A feature of the proposed method of processing the etching solution is the AMF activation of the ferritization process. At the same time, the energy efficiency of the process of treating spent solutions is significantly increased since electricity consumption decreases by more than 40 % compared to thermal activation of the process [18]. The results of this work strongly suggest that AMF activation does not impair the degree of extraction of iron ions from the reaction mixture compared to traditional thermal activation.…”
Section: Discussion Of Results Of Processing Spent Etching Solutions ...mentioning
confidence: 73%
“…The disadvantages of hydro-phase ferritization are high energy consumption since it is carried out at temperatures above 75 °C [17]. Paper [18] shows that an alternative to thermal hydro-phase ferritization is the activation of the process by alternating magnetic fields (AMF activation) at room temperatures. The studies were conducted at a high amplitude of magnetic induction (0.3 Tl), which leads to significant cost of electrical energy to activate the reaction mixture during ferritization.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The course of the ferritization process is influenced by a number of technological factors that determine the type of primary embryonic iron-containing structures, their formation, and further development with the formation of stable compounds with different particle sizes and shapes. Among these factors are the initial concentration of iron ions [29], the pH value [30], the temperature [31,32], the process duration [33], and the oxidizer (air oxygen) consumption [34]. In addition, the above factors can affect the formation of a certain modification of iron hydroxides and oxyhydroxides and their subsequent transformation into other more stable oxide compounds in an alkaline medium [35].…”
Section: Introductionmentioning
confidence: 99%